Law of Double Negation: Reciprocity and Transposition of Negatives

如果你也在线性代数linearalgebra这个学科遇到相关的难题,请随时添加vx号联系我们的代写客服。我们会为你提供专业的服务。 linearalgebra™长期致力于留学生网课服务,涵盖各个网络学科课程:金融学Finance,经济学Economics,数学Mathematics,会计Accounting,文学Literature,艺术Arts等等。除了网课全程托管外,linearalgebra™也可接受单独网课任务。无论遇到了什么网课困难,都能帮你完美解决!

0.17 Law of Double NegationMoreover this reciprocity is general: if a term \(b\) is the negative of the term \(a\), then the term \(a\) is the negative of the term \(b\). These two statements are expressed by the same formulas\[ab=0,\quad a+b=1,\]and, while they unequivocally determine \(b\) in terms of \(a\), they likewise determine \(a\) in terms of \(b\). This is due to the symmetry of these relations, that is to say, to the commutativity of multiplication and addition. This reciprocity is expressed by the _law of double negation_\[(a^{\prime})^{\prime}=a,\]which may be formally proved as follows: \(a^{\prime}\) being by hypothesis the negative of \(a\), we have\[aa^{\prime}=0,\quad a+a^{\prime}=1.\]On the other hand, let \(a^{\prime\prime}\) be the negative of \(a^{\prime}\); we have, in the same way,\[a^{\prime}a^{\prime\prime}=0,\quad a^{\prime}+a^{\prime\prime}=1.\]But, by the preceding lemma, these four equalities involve the equality\[a=a^{\prime\prime}.\]Q. E. D.This law may be expressed in the following manner:If \(b=a^{\prime}\), we have \(a=b^{\prime}\), and conversely, by symmetry.This proposition makes it possible, in calculations, to transpose the negative from one member of an equality to the other.The law of double negation makes it possible to conclude the equality of two terms from the equality of their negatives (if \(a^{\prime}=b^{\prime}\) then \(a=b\)), and therefore to cancel the negation of both members of an equality.From the characteristic formulas of negation together with the fundamental properties of \(0\) and \(1\), it results that every product which contains two contradictory factors is null, and that every sum which contains two contradictory summands is equal to \(1\).In particular, we have the following formulas:\[a=ab+ab^{\prime},\quad a=(a+b)(a+b^{\prime}),\]which may be demonstrated as follows by means of the distributive law:\[a=a\times 1=a(b+b^{\prime})=ab+ab^{\prime},\] \[a=a+0=a+bb^{\prime}=(a+b)(a+b^{\prime}).\]These formulas indicate the principle of the method of development which we shall explain in detail later (SSSS0.21 sqq.)

发表回复

您的电子邮箱地址不会被公开。 必填项已用 * 标注